Systemic lupus erythematosus: Diagnosis and clinical management - Fava, Andrea; Petri, Michelle (Journal of autoimmunity, 2019)
Systemic lupus erythematosus (SLE) is a worldwide chronic autoimmune disease which may affect every organ and tissue. Genetic predisposition, environmental triggers, and the hormonal milieu, interplay in disease development and activity. Clinical manifestations and the pattern of organ involvement are widely heterogenous, reflecting the complex mosaic of disrupted molecular pathways converging into the SLE clinical phenotype. The SLE complex pathogenesis involves multiple cellular components of the innate and immune systems, presence of autoantibodies and immunocomplexes, engagement of the complement system, dysregulation of several cytokines including type I interferons, and disruption of the clearance of nucleic acids after cell death. Use of immunomodulators and immunosuppression has altered the natural course of SLE. In addition, morbidity and mortality in SLE not only derive from direct immune mediated tissue damage but also from SLE and treatment associated complications such as accelerated coronary artery disease and increased infection risk. Here, we review the diagnostic approach as well as the etiopathogenetic rationale and clinical evidence for the management of SLE. This includes 1) lifestyle changes such as avoidance of ultraviolet light; 2) prevention of comorbidities including coronary artery disease, osteoporosis, infections, and drug toxicities; 3) use of immunomodulators (i.e. hydroxychloroquine and vitamin D); and 4) immunosuppressants and targeted therapy. We also review new upcoming agents and regimens currently under study. •Classification criteria are a helpful diagnostic framework to confirm clinical judgement.•Hydroxychloroquine is the cornerstone of medical therapy in lupus.•Immunosuppression and targeted therapies are paramount for renal and severe extra-renal lupus manifestations.•New therapies targeting the Th17, BAFF, JAK/STAT, and calcineurin pathways showed positive phase 2b trial results.